Abnormalities in the copper transporter CTR1 in postmortem hippocampus in schizophrenia: A subregion and laminar analysis - Schoonover, Kirsten E.; Farmer, Charlene B.; Morgan, Charity J.; Sinha, Vidushi; Odom, Laura; Roberts, Rosalinda C. (Schizophrenia research, 2021)
Dysbindin-1 modulates copper transport, which is crucial for cellular homeostasis. Several brain regions implicated in schizophrenia exhibit decreased levels of dysbindin-1, which may affect copper homeostasis therein. Our recent study showed decreased levels of dysbindin-1, the copper transporter-1 (CTR1) and copper in the substantia nigra in schizophrenia, providing the first evidence of disrupted copper transport in schizophrenia. In the present study, we hypothesized that there would be lower levels of dysbindin-1 and CTR1 in the hippocampus in schizophrenia versus a comparison group. Using semi-quantitative immunohistochemistry for dysbindin1 and CTR1, we measured the optical density in a layer specific fashion in the hippocampus and entorhinal cortex in ten subjects with schizophrenia and ten comparison subjects. Both regions were richly immunolabeled for CTR1 and dysbindin1 in both groups. In the superficial layers of the entorhinal cortex, CTR1 immunolabeled neuropil and cells showed lower optical density values in patients versus the comparison group. In the molecular layer of the dentate gyrus, patients had higher optical density values of CTR1 versus the comparison group. The density and distribution of dysbindin-1 immunolabeling was similar between groups. These laminar specific alterations of CTR1 in schizophrenia suggest abnormal copper transport in those locations.